Endometrioma masquerading an ovarian carcinoma - Sidhu, Amanat; Bala, Ripan; Tandon, Pooja; Chhina, Rajdeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Endometriosis is the presence of endometrial tissue outside the uterus. Endometriosis affects 10-15% of all women in reproductive age group and 70% of the women with chronic pelvic pain. The risk of malignant transformation in an endometrioma has been reported to be low, though there is an increased risk for certain gynecological as well as non-gynecological carcinomas with endometriosis. We present a case diagnosed as having endometrioma transforming into a malignant tumor in a young female. We intend to emphasize that all the clinicians should make their patients aware of the malignant potential of endometriosis and a strict follow up of all cases being treated conservatively should be a must.